La nécropole de l’âge du Bronze des Pâtures à Saumeray (Eure-et-Loir) : mise en évidence de gestes funéraires originaux - Patrice Georges; Tony Hamon (Revue Archéologique du Centre de la France)
A rescue excavation of a Bronze Age burial ground was carried out on the site of Saumeray, at Les Pâtures during the winter of 2001-2002. The systematic excavation of the cremation pits, many of which had left only ephemeral traces, showed that most of them contained fragments of burnt bone, the quantity of which never exceeded a few grams. The study of this material, both on site and during post-excavation work, aimed to reconstruct the series of actions related to the cremation and the inhumation of the cremated remains. This study showed that the cremation in itself represents only one stage, albeit very important, in the process by which the group dealt with their deceased. The observations of one of the monuments allow us to propose several hypotheses concerning the nature and the functions of these circular enclosures in this area of the Loir valley.